SAW propagation in periodic arrays including temperature effects - Wallner, Paul; Ruile, Werner; Weigel, Robert (IEEE Ultrasonics Symposium 1999, 1999)
In order to calculate the temperature behavior of SAW propagation in infinite periodic arrays a numerical procedure was established improving the theory of previous studies. This theory is based upon the orthogonal integration method. Improvements include a consideration of the mass loading effect due to the metal grating, a better numerical performance of the software and full access for calculations in the frequency range of both, stopband and conversion. Including the temperature dependence calculations were performed for quartz and LiTaO 3 leaky-SAW crystal cuts. The temperature behavior of stopband center frequency and width, attenuation, and onset-frequency was investigated and compared to results obtained for homogenous structures
elib2cris::1512001600,wallner1999b
Keywords: SAW